Pencegahan Korosi Kapal Dengan Metode Pengecatan - Salim Salim (Sekolah Tinggi Maritim Yogyakarta, 2019)
One of the biggest sources of damage to ships and other floating devices is corrosion caused by floating vehicles / tools in the sea water environment. Negligence or lack of perfection of protection against seawater corrosion attacks will be very detrimental. One way to reduce greater losses due to corrosion attacks is by passive prevention. Passive prevention is by painting. Painting the vessel / floating tool aims to complicate or inhibit the occurrence of symptoms of growth and development of the occurrence of corrosion. Implementation of ship painting is carried out in two (2) stages of activities, namely cleaning the ship's body and continuing painting. The good quality of the painting depends on the quality of the material of the vessel, the quality of the paint, the type and method of cleaning the construction, the type and manner of painting and the skills and experience of the painters. Painting results will affect the ability of paint to protect ship construction against seawater corrosion attacks.